Boundary behavior of solutions of elliptic operators in divergence form with a BMO anti-symmetric part. Issue 2 (1st February 2019) - Li, Linhan; Pipher, Jill
Abstract: In this article, we investigate the boundary behavior of solutions of divergence-form operators with an elliptic symmetric part and a BMO antisymmetric part. Our results will hold in non-tangentially accessible (NTA) domains; these general domains were introduced by Jerison and Kenig and include the class of Lipschitz domains. We establish the Hölder continuity of the solutions at the boundary, existence of elliptic measures ω L associated to such operators, and the well-posedness of the continuous Dirichlet problem as well as theL p ( d ω ) Dirichlet problem in NTA domains. The equivalence in the L p norm of the square function and the non-tangential maximal function under certain conditions remains valid. When specialized to Lipschitz domains, it is then possible to extend, to these operators, various criteria for determining mutual absolute continuity of elliptic measure with surface measure.